The city of Mayafariqin through Arab sources (581-658 AH / 1184-1260 AD) A cultural, political study (Journal of the College of Basic Education, 2022)
The subject of the research included Mayafariqin through the Arab sources, the time period (581/658 AH) (1184-1260 AD), which is the period extending from Sultan Salah al-Din al-Ayyubi's seizure of the city and its affiliated businesses until its fall as a result of the Tatar attacks in the year (659 AH - 1261 AD) after the fall of Cities of the Levant in the year (658 AH - 1260 AD).The topic of the research included a brief historical overview of the city during the Islamic conquest period, as well as the most important cultural centers in the city such as castles and fortresses, etc. The research also dealt with the cultural life of the city.